SUBJECTIVE NORM, ATTITUDES, TRUST, TERHADAP PURCHASE INTENTIONS PADA BUAH DAN MAKANAN ORGANIK - AILEN TANIA; DENNY SEPTA HARYANTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The purpose of this research is to understand how information revealed on organic food label drive consumer trust and attitudes toward organic foods, which in turn together with subjective norm eventually influence subsequent purchase intentions of consumption on organic food in north Jakarta. This research used a quantitative method and use primary data such as respondent answer. Researcher used questionnaire to collect data from 100 respondent from Total Fresh Fruit supermarket at north Jakarta. In total, 100 valid questionnaires were obtained, yielding a response rate of 100 per cent. Researcher analysis the data using multiple linear regression with SPSS 25.0 for windows. The result showed attitudes, trust significantly effects purchase intentions of consumption on fruit and organic food, but the result with subjective norm is inversely proportional. Because most people buy organic food product at north Jakarta negatively not based by social pressure for a person to engage in or avoid a behavior effected by those people who important for them.